The early childhood oral health impact scale (ECOHIS): Assessment tool in oral health related quality of life - Ismail, Nur Syafiqah; Abdul Ghani, Nurul Murshidah; Supaat, Salwana; Kharuddin, Azrul Fazwan; Ardini, Yunita Dewi (University of Dicle, 2018)
Oral health related quality of life (OHRQoL) defines as the physical and psychological satisfaction with oral health status and the condition of the teeth. The objective of this study was to quantify the impacts of oral health related quality of life among Malaysia preschool children and their caregivers by using Early Childhood Oral Health Impact Scale (ECOHIS). A cross-sectional survey was conducted among preschool children under 5 years old and below from IIUM dental clinic and preschools around Kuantan within 10 months from January until October 2016. This research was approved by the IIUM Research Ethic Committee (IREC). Inter-examiner reliability was tested with Kappa statistic (0.81). A clinical oral examination was performed and decayed-missing-filled teeth (dmft) was documented. Parents or caregivers answered and completed the ECOHIS questionnaire. Data were analyzed by structural equation modelling (SEM) using SPSS and Amos® package version 23.0 with significance level was set at ∝< 0.05. 130 samples were analyzed. The mean of children's age and dmft were 4.22 and 3.98. Cronbach's alpha for ECOHIS was 0.900, respectively child and family sections were 0.880 and 0.843. Patient's age, ECOHIS and dmft were significantly associated (p<0.05). Age has statistically significant direct and indirect relationship with child psychological factor, family factor towards dmft. Oral Health has an impact on quality of life in Malaysian preschool children and their caregivers. Full SEM proved ECOHIS as a tool for assessing the impact of oral disorder on quality of life of Malaysian preschool children in Kuantan